Use of MSC.Adams Software Product in Modelling Vibration Sources - Sapietova, Alzbeta; Dekys, Vladimir (Communications - Scientific letters of the University of Zilina, 2016)
This paper presents the methodology of rotating device modelling in order to facilitate correct evaluation of selected, usually malfunction (degraded) states of rotating machines of mechanical systems, especially of gearboxes. The analysis was performed using mathematical models utilising MSC.ADAMS software product to solve the dynamics of a system of bodies. The correctness of the proposed method is verified by qualitative comparison of simulation results with the presented symptoms of malfunction states and also by comparison with real measurement results from technical practice.